2022
DOI: 10.1093/nar/gkac503
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and ethnicity-independent hypervariable DNA methylation states show evidence of establishment in the early human embryo

Abstract: We analysed DNA methylation data from 30 datasets comprising 3474 individuals, 19 tissues and 8 ethnicities at CpGs covered by the Illumina450K array. We identified 4143 hypervariable CpGs (‘hvCpGs’) with methylation in the top 5% most variable sites across multiple tissues and ethnicities. hvCpG methylation was influenced but not determined by genetic variation, and was not linked to probe reliability, epigenetic drift, age, sex or cell heterogeneity effects. hvCpG methylation tended to covary across tissues … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 114 publications
3
7
0
Order By: Relevance
“…Expanding on this, it has also been reported that highly variable sites are found at imprinted control regions (17). Through investigation of the genes annotated to our VMPs, we also found 21 VMPs identified in our analysis annotated to the gene HOXA5, a gene predicted to be maternally imprinted.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Expanding on this, it has also been reported that highly variable sites are found at imprinted control regions (17). Through investigation of the genes annotated to our VMPs, we also found 21 VMPs identified in our analysis annotated to the gene HOXA5, a gene predicted to be maternally imprinted.…”
Section: Discussionsupporting
confidence: 71%
“…To this effect, previous studies have aimed to characterise a catalogue of loci showing highly variable DNA methylation in a range of tissues including peripheral blood, cord blood, saliva, placenta and colon (12; 13; 14; 15; 16; 17). Nevertheless, this is a difficult task due to the dynamic nature of the epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…4B and fig. S10) ( 33 ). However, analyses of neuronal cultures after 26 days of differentiation showed significantly increased POMC DNA methylation in all cultures conducted with SFX-E8/depleted medium, irrespective of the addition of individual C1 metabolites [nested t test with different time points as columns (1) and C1 metabolite groups as subcolumns (2), P (1) < 0.0001, P (2) < 0.0001] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This type of POE is mainly introduced by genomic imprinting, which is established at early developmental stages and needs to be well maintained/regulated throughout the life (16). The epigenomic features influenced by typical POEs has been found to be sensitive to prenatal and postnatal environmental stimuli, such as maternal nutrition during pregnancy and stress accompanied with assisted reproductive technologies (15,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…This type of POE is mainly introduced by genomic imprinting, which is established at early developmental stages and needs to be well maintained/regulated throughout the life(16). The epigenomic features influenced by typical POEs has been found to be sensitive to prenatal and postnatal environmental stimuli, such as maternal nutrition during pregnancy and stress accompanied with assisted reproductive technologies(15, 1922). In addition to the methylation sites influenced by the typical POE, a different set of methylation sites also display imbalanced methylation similarity between nuclear family members of the same genetic distance, but without regulatory POE-mQTLs being detected, and are not enriched in known imprinted regions.…”
Section: Introductionmentioning
confidence: 99%